Determinants of Investment Decision Making Behavior (Empirical Study on MSMEs in Semarang City) - Harjito, R. Rachmiyantono Wahju (Untag Business and Accounting Review, 2022)
The purpose of this study was to determine the effect of financial attitudes, financial literacy and locus of control on investment decisions. This research is a quantitative study with a sample of 112 micro, small and medium enterprises (MSMEs) in Semarang City. The data analysis model used is multiple linear regression. The results of the study show that financial attitudes, financial literacy, and locus of control have a positive effect on investment decisions. The implication of this study is that MSME owners in Semarang City are expected to be well planned and structured in managing their finances, increasing investment information, and preparing budgets appropriately.